A new species of Passiflora L. (Passifloraceae) from Guerrero and Oaxaca, México - Lozada‒Pérez, Lucio; Gutiérrez, Jorge Fernando Rojas (Phytotaxa, 2016)
Passiflora quadraticordata, a new species of Mexican flora with uncinate trichomes, is herein described and illustrated. This species is endemic to the southern Sierra Madre of the states of Guerrero and Oaxaca, México, and belongs to the subgenus Decaloba and the supersection Bryonioides.